Online video usage in undergraduate research presentations and learning satisfaction: a comparative study of male and female students / Nurul Hidayana Mohd Noor and Hasnatulsyakhira Abdullah Hadi - Mohd Noor, Nurul Hidayana; Abdullah Hadi, Hasnatulsyakhira (UiTM Press, 2025)
The academic field is an important learning platform in a country’s education system and students are valuable assets to the country. The primary purpose of this study was to identify gender-related differences in the relationships among perceived usefulness, perceived ease of use, attitude, need for achievement, and learning satisfaction with the use of online videos for undergraduate research project presentations. Specifically, this paper studies the mediating effect of the need for achievement on the proposed relationships. The study employed a cross-sectional survey with systematic sampling. The data were collected from 200 students at the Faculty of Administrative Science and Policy Studies, Universiti Teknologi MARA (UiTM). The model was tested using Structured Equation Modelling (SEM). The findings can be summarised as follows: (i) both female and male students’ learning satisfaction is influenced by perceived usefulness, perceived ease of use, and attitude, and (ii) both males and females are expected to have a high need for achievement, with female students requiring a more goal-oriented personality than male students to perform well in their learning. The findings provide practical support for the development of new educational strategies to assist universities, faculties, and higher learning institutions in enhancing their existing student development programs or projects.